Design of a Batik Coloring Waste Treatment Tool Using the Electrocoagulation Method with a Capacity of 50 Liters - Asni Tafrikhatin; Hendi Purnata; Nitis Aruming Firdaus (Politeknik Piksi Ganesha Indonesia, 2023)
Batik coloring still uses synthetic dyes, so the disposal of coloring waste should not be careless. Most batik craftsmen process their batik waste by settling the waste liquid for a long time. The process is very ineffective. The purpose of this research is to design a batik processing tool that is cheap and effective. The research method uses the electrocoagulation method. The electrocoagulation method is an electrochemical water treatment. The design of this batik waste treatment tool consists of five parts including: (1) Electrocoagulation Tub, (2) Skimmer, (3) Electrode, (4) Sand Filter, and (5) Studge Drying Bed. This tool works with 900 watts of power with an output of 20-40 volts DC. The capacity of liquid waste is 50 liters. Duration of waste treatment for 2 hours. The electrocoagulation method is able to reduce the values of BOD5, COD, TSS, and TDS in batik dye waste. The pH of wastewater which is still high can be reduced by giving alum.